DOI: 10.17077/etd.qelsdur7
|View full text |Cite
|
Sign up to set email alerts
|

A metaphilosophy of naturalism

Abstract: Fales. I also thank my students for not only helping me sharpen my pedagogy but also for the many lessons that they have given me. Additionally, I am grateful to my colleagues and friends throughout my education, all of whom have been stimulating, worthy interlocutors and gadflies.Finally, for her resolute, steadfast devotion and support-emotional, intellectual, moral, and more-I am extraordinarily thankful to my partner, confidant, and best friend, Hanna G. Childers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 269 publications
(368 reference statements)
0
2
0
Order By: Relevance
“…As noted above, most recent work has focused on the effect of detector noise and resolution on the signal-to-noise ratio (SNR) of OP/FT-IR spectra (3)(4)(5)(6). Griffiths et al (4) have shown that the noise level on the baseline of an absorbance spectrum is directly proportional to the resolution, ∆v, when detector noise is dominant.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, most recent work has focused on the effect of detector noise and resolution on the signal-to-noise ratio (SNR) of OP/FT-IR spectra (3)(4)(5)(6). Griffiths et al (4) have shown that the noise level on the baseline of an absorbance spectrum is directly proportional to the resolution, ∆v, when detector noise is dominant.…”
Section: Introductionmentioning
confidence: 99%
“…140 For instance, a Washington Supreme Court decision reasoned that since a college education is a necessity, not a luxury, a student who does not have one is at a disadvantage in the job market. 141 The Childers court, like other state Supreme Courts resolving the issue, used a rational basis review to uphold the duty to pay a post-minority child's college education because the state has a strong legitimate interest in ensuring that all of its citizens receive an education, 142 especially citizens from broken homes because children of divorced parents face more economic disadvantages than children from intact homes. 143 Other commentators, however, argue that the law should not force divorced parents to contribute to post-minority education of their children by analogizing their reasoning to the freedom of parents to disinherit minor children.…”
Section: Post-minority Support For Education In Divorce Lawmentioning
confidence: 99%